A person‐centred approach to implementation of psychosocial interventions with people who have an intellectual disability and dementia—A participatory action study. Issue 1 (18th August 2020) - Watchman, Karen; Mattheys, Kate; McKernon, Michael; Strachan, Heather; Andreis, Federico; Murdoch, Jan
Abstract: Background: Numbers of people with an intellectual disability and dementia present a global health and social challenge with associated need to reduce stress or agitation and improve quality of life in affected individuals. This study aimed to identify effectiveness of psychosocial interventions in social care settings and, uniquely, explore use of photovoice methodology to develop dialogue about dementia. Methods: This mixed‐method participatory action study used individualised goal‐setting theory with 16 participants with intellectual disability and dementia, and 22 social care staff across 11 sites. Five co‐researchers with intellectual disability were part of an inclusive research team collecting data using existing and bespoke tools including photovoice. Analysis used descriptive and inferential statistics and framework analysis. Results: Seventy four percentage of individual goals met or exceeded expectations with reduction in some "as required" medication. Qualitative findings include themes of enabling care and interventions as tools for practice. Photovoice provided insight into previously unreported fears about dementia. Conclusions: Individualized psychosocial interventions have potential to reduce distress or agitation.